Cooperative Encoding and Decoding of Mixed Delay Traffic under Random-User Activity - Nikbakht, Homa; Wigger, Michele; Shitz, Shlomo Shamai; Gorce, Jean-Marie (2021 IEEE Information Theory Workshop (ITW), 2021)
This paper analyses the multiplexing gain (MG) achievable over Wyner's symmetric network with random user activity and random arrival of mixed-delay traffic. The mixed-delay traffic is composed of delay-tolerant traffic and delay-sensitive traffic where only the former can benefit from transmitter and receiver cooperation since the latter is subject to stringent decoding delays. The total number of cooperation rounds at transmitter and receiver sides is limited to D rounds. We derive inner and outer bounds on the MG region. In the limit as D→∞, the bounds coincide and the results show that transmitting delaysensitive messages does not cause any penalty on the sum MG. For finite D our bounds are still close and prove that the penalty caused by delay-sensitive transmissions is small.